PENERAPAN MEDIA UBUR-UBUR EDUKASI TERHADAP HASIL BELAJAR KOGNITIF IPAS PESERTA DIDIK - A. Nur Aliza Mauliana; Dewi Hikmah Marisda; Nurul Maghfirah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe students’ cognitive learning outcomes in Integrated Science and Social Studies (IPAS) before and after the implementation of the Educational Jellyfish Media (UBUD), and to analyze the improvement in learning outcomes after its application. This research employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest model. The study was conducted at SDN No. 228 Tunreng Tellue, Bone Regency, South Sulawesi, involving 24 fourth-grade students selected through saturated sampling. Data were collected using multiple-choice tests (pretest and posttest), observation sheets, and documentation. The instruments were validated through expert judgment using Gregory’s formula, resulting in very high validity coefficients (0.9–1.0). Data analysis techniques included descriptive statistics and N-Gain analysis to measure learning improvement. The results showed that students’ cognitive learning outcomes before the implementation of UBUD were categorized as low, with a mean pretest score of 48.17 and low classical completeness. After the implementation, the posttest results significantly improved, with a mean score of 83.00 and 100% classical completeness. The N-Gain score was 0.68, indicating a moderate level of improvement. These findings suggest that the Educational Jellyfish Media (UBUD) is effective in enhancing students’ cognitive learning outcomes in IPAS. The use of interactive and game-based learning media successfully increased student engagement, motivation, and conceptual understanding. In conclusion, UBUD serves as an effective and innovative instructional medium that can improve learning outcomes and create a more engaging and student-centered learning environment in elementary education.